2002
DOI: 10.1002/rcm.610
|View full text |Cite
|
Sign up to set email alerts
|

A straightforward means of coupling preparative high‐performance liquid chromatography and mass spectrometry

Abstract: Flow splitting to a mass spectrometer is a common way of coupling a highly specific detector to preparative or semi-preparative high-performance liquid chromatography (HPLC) purification of combinatorial libraries, drug metabolites, and characterizable impurities. The sensitive mass spectrometer consumes only a small fraction of the analyte while providing online structure-specific detection, and its output can thus be used to trigger collection of the desired fraction. Coupling mass spectrometry to preparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The total recovery percentage of effluent ( TR ) collected from CPC and which was not used for the MS analysis, as well as the percentage of effluent lost from the MS detection ( EL ), can be calculated from Eqn. (1):24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total recovery percentage of effluent ( TR ) collected from CPC and which was not used for the MS analysis, as well as the percentage of effluent lost from the MS detection ( EL ), can be calculated from Eqn. (1):24 …”
Section: Resultsmentioning
confidence: 99%
“…A simple approach to solve this problem and generate smooth peak profiles consisted in increasing the scan time from 0.2 to 0.8 s, as indicated in Fig. 2 24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both active and passive splitting devices have been successfully incorporated into instrumental setups for mass-triggered fractionation [3,12,15,16]. A comparison of active and passive splitters for preparative HPLC has shown that active splitting devices (also called mass rate attenuators) offer minimal peak broadening and easy adaptation to a broad range of flow rates, split ratios, and make-up flows [17]. Nevertheless, due to abrasion of the rapidly moving parts, rotor seals have to be exchanged on a regular basis.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the maintenance aspect, the employment of active splitters adds additional acoustic noise exposure to working environments. Moreover, peak profiles need to be smoothed by suitable averaging because of the discontinuous transfer of liquid between the donor and acceptor stream [17]. Passive splitters, on the other hand, are more difficult to optimize but hold the advantage of null maintenance and noise level, and continuous transfer of liquid from one effluent stream to the other.…”
Section: Introductionmentioning
confidence: 99%